Soil bacterial biodiversity characterization by flow cytometry: The bottleneck of cell extraction from soil. Issue 7 (4th May 2022) - El Mujtar, Verónica A.; Chirdo, Fernando; Lagares, Antonio; Wall, Luis; Tittonell, Pablo
Abstract: The importance of soil biodiversity is increasingly recognized in agriculture and natural resource research and development. Yet, traditional soil biodiversity assessments are costly and time‐consuming, limiting the extent and frequency of sampling and analysis in space and time. Flow cytometry (FCM) is a powerful technique to characterize cell communities due to its high robustness and accuracy, requiring only a short time for the characterization. Therefore, FCM could expand soil research capabilities by allowing the characterization of different aspects of bacterial biodiversity. However, this implementation of FCM requires the previous dispersion, separation and purification of bacteria from complex soil matrices. Moreover, soil monitoring programs or evaluation of soil management practices require high‐throughput analysis. In this context, soil processing protocols need to consider not only an adequate recovery of undamaged, representative and pure soil bacteria, but also short‐time processing requirements. Although soil processing protocols have been reported over time, to our knowledge, there is no recommended soil extraction protocol for high‐throughput analysis of bacterial biodiversity by FCM. We reviewed the state‐of‐art of the use of flow cytometry in scientific research and the protocols used for the extraction of bacteria from soil. We analysed the literature to take stock of the diversity of methodologies for soil processing and applications of flow cytometry in bacterial characterization considering abundance, diversity, community structure and functional properties. This review provides several lines of evidence of the use of flow cytometry for soil bacterial biodiversity (SBB) characterization, highlighting its potential for soil monitoring and studies on soil bacterial community dynamics. The review also highlights and discusses the most relevant constraints and research gaps that need to be considered for high‐throughput analysis of SBB by FCM, such as evaluation of scale‐down, new reagents for and methods of purification, threshold of bacterial recovery efficiency and selection of a standardized and validated protocol. We proposed a protocol for soil bacterial extraction for high‐throughput analysis of SBB by FCM and we provided detailed databases of systematized information that would be useful to the scientific community. Abstract: La importancia de la biodiversidad edáfica es reconocida en áreas de investigación y desarrollo en agricultura y recursos naturales. Sin embargo, la caracterización de la biodiversidad edáfica es costosa en términos económicos y técnicos, limitando la cobertura y frecuencia de los muestreos y análisis espaciales y temporales. La citometría de flujo es una técnica poderosa para la caracterización de comunidades de células debido a su alta robustez y precisión, requiriendo sólo cortos períodos de tiempo. Por tanto, la citometría de flujo podría ampliar nuestra capacidad de investigación en suelos permitiendo la caracterización de diferentes aspectos de la biodiversidad bacteriana. Sin embargo, esta implementación de la citometría de flujo requiere previamente de la dispersión, separación y purificación de bacterias desde complejas matrices de suelo. Además, los programas de monitoreo o evaluación de prácticas de manejo del suelo requieren alto rendimiento en los análisis. En este contexto los protocolos de procesamiento de suelos deben considerar no sólo una recuperación adecuada de bacterias de suelo intactas, representativas y puras, sino también tiempos cortos de procesamiento. Aunque a lo largo del tiempo se han reportado protocolos de procesamiento de suelo, no conocemos que exista un protocolo recomendado para análisis de alto rendimiento de biodiversidad bacteriana por citometría de flujo. Por tanto, realizamos una revisión del estado del arte del uso de la citometría de flujo en investigación científica y de los protocolos de extracción de bacterias a partir del suelo. Analizamos la literatura para conocer las metodologías de procesamiento de suelo y las aplicaciones de la citometría de flujo en la caracterización bacteriana considerando abundancia, diversidad, estructura de comunidades y propiedades funcionales. Esta revisión brinda evidencias del uso de la citometría de flujo en la caracterización de la biodiversidad bacteriana edáficas, destacando su potencial para el monitoreo de suelo y estudios de dinámica de comunidades bacterianas edáfica. La revisión también destaca y discute las limitantes y vacíos de información más relevantes que se deben considerar para un análisis de alto rendimiento de la biodiversidad bacteriana edáfica mediante citometría de flujo, tales como la evaluación del escalado hacia abajo, nuevos reactivos y métodos de purificación, umbrales de eficiencia de recuperación de bacterias y selección de un protocolo validado y estandarizado. Proponemos un protocolo para la extracción de bacterias de suelo para análisis de alto rendimiento de la biodiversidad bacteriana edáfica mediante citometría de flujo y proporcionamos bases de datos detalladas de información sistematizada que puede ser útiles para futuras investigaciones de la comunidad científica.